Widespread use of unconventional targeting signals in mitochondrial ribosome proteins. (17th November 2021) - Bykov, Yury S; Flohr, Tamara; Boos, Felix; Zung, Naama; Herrmann, Johannes M; Schuldiner, Maya
Abstract: Mitochondrial ribosomes are complex molecular machines indispensable for respiration. Their assembly involves the import of several dozens of mitochondrial ribosomal proteins (MRPs), encoded in the nuclear genome, into the mitochondrial matrix. Proteomic and structural data as well as computational predictions indicate that up to 25% of yeast MRPs do not have a conventional N‐terminal mitochondrial targeting signal (MTS). We experimentally characterized a set of 15 yeast MRPs in vivo and found that five use internal MTSs. Further analysis of a conserved model MRP, Mrp17/bS6m, revealed the identity of the internal targeting signal. Similar to conventional MTS‐containing proteins, the internal sequence mediates binding to TOM complexes. The entire sequence of Mrp17 contains positive charges mediating translocation. The fact that these sequence properties could not be reliably predicted by standard methods shows that mitochondrial protein targeting is more versatile than expected. We hypothesize that structural constraints imposed by ribosome assembly interfaces may have disfavored N‐terminal presequences and driven the evolution of internal targeting signals in MRPs. Synopsis: Unlike most mitochondrial matrix proteins synthesized in the cytosol, many subunits of mitochondrial ribosomes lack N‐terminal targeting sequences. Dissection of Mrp17 reveals TOM‐binding sites and multiple positive charges as directive elements for mitochondrial targeting and translocation. 25% of mitochondrial ribosomal proteins (MRPs) lack predicted N‐terminal matrix‐targeting presequences. 5 out of 15 studied MRPs utilize internal mitochondrial targeting determinants. Dissection of Mrp17/bS6m reveals an internal sequence carrying its targeting information. The Mrp17 internal signal contains TOM‐complex binding sites for targeting and scattered positive charges for translocation. Abstract : Possibly due to structural constraints, a subset of cytosolically synthesized mitochondrial matrix proteins is targeted via internal sequences, rather than prepeptides.